Normalization Methods for the Analysis of Unbalanced Transcriptome Data: A Review - Liu, Xueyan; Li, Nan; Liu, Sheng; Wang, Jun; Zhang, Ning; Zheng, Xubin; Leung, Kwong-Sak; Cheng, Lixin (Frontiers in Bioengineering and Biotechnology, 2019)
Dozens of normalization methods for correcting experimental variation and bias in high-throughput expression data have been developed during the last two decades. Up to 23 methods among them consider the skewness of expression data between sample states, which are even more than the conventional methods, such as loess and quantile. From the perspective of reference selection, we classified the normalization methods for skewed expression data into three categories, data-driven reference, foreign reference, and entire gene set. We separately introduced and summarized these normalization methods designed for gene expression data with global shift between compared conditions, including both microarray and RNA-seq, based on the reference selection strategies. To our best knowledge, this is the most comprehensive review of available preprocessing algorithms for the unbalanced transcriptome data. The anatomy and summarization of these methods shed light on the understanding and appropriate application of preprocessing methods.